2018
DOI: 10.1098/rspb.2018.1894
|View full text |Cite
|
Sign up to set email alerts
|

Globally invasive genotypes of the amphibian chytrid outcompete an enzootic lineage in coinfections

Abstract: Competition between genotypes is likely to be a key driver of pathogen evolution, particularly following a geographical invasion by distant strains. Theory predicts that competition between disease strains will result in the most virulent strain persisting. Despite its evolutionary implications, the role of strain competition in shaping populations remains untested for most pathogens. We experimentally investigated the in vivo competitive differences between two divergent lineages of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…Their protective effect against disease is associated with several traits that correlate with their colonisation ability and invasiveness: expression and function of Bd crinkler genes, metalloproteases and other effector proteins. However, the hypervirulent isolate's high fecundity, marked invasiveness in amphibian cells and more pronounced colonization capacity in vivo suggest a distinct competitive advantage over the local isolates 39 . Moreover, co-infections may result in superinfection and/or hybridisation 3,40,41 , with highly unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Their protective effect against disease is associated with several traits that correlate with their colonisation ability and invasiveness: expression and function of Bd crinkler genes, metalloproteases and other effector proteins. However, the hypervirulent isolate's high fecundity, marked invasiveness in amphibian cells and more pronounced colonization capacity in vivo suggest a distinct competitive advantage over the local isolates 39 . Moreover, co-infections may result in superinfection and/or hybridisation 3,40,41 , with highly unpredictable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Batrachochytrium, or with various combinations of lineages of Bd that differ in genotype (Jenkinson et al, 2018;Longo, Fleischer, & Lips, 2019;Ossiboff et al, 2019). Bd is widespread, and one or more lineages can be found on all continents inhabited by amphibians, including North America (O'Hanlon et al, 2018).…”
Section: Chytrid Coinfection Can Occur Between the Two Species Ofmentioning
confidence: 99%
“…If Bd ‐ GPL introduced to Bolivia via the cloud forests in the 1990s has indeed been transported to the altiplano by waterfowl (Burrowes & De la Riva, 2017b; Garmyn et al., 2012; Johnson & Speare, 2005) or other potential vectors, it would explain the recent declines of certain altiplano species such as Rhinella spinulosa and Telmatobius marmoratus among others (De la Riva & Reichle, 2014), as well as its presence in extant T. culeus from Lago Titicaca. This hypervirulent strain ( Bd‐GPL ) with its aggressive infection advantage (Jenkinson et al., 2018) could potentially outcompete older endemic strains and put at risk populations that survived what may have been an old, historically unassessed, Bd epidemic (‘the ghost of Bd past’) likely caused by a Bd genotype that has been either extirpated, or not detected in this preliminary study.…”
Section: Discussionmentioning
confidence: 90%
“…Few places are known to contain multiple lineages (Byrne et al., 2019; O’hanlon et al., 2018; Schloegel et al., 2012), and this may speak to the ability of Bd‐GP L to outcompete enzootic lineages. Recent findings have shown that when Bd‐GPL and the older Brazilian strain (now considered Bd ‐ASIA‐2/ Bd ‐BRAZIL; see O’hanlon et al., 2018) are co‐inoculated onto a single host, Bd‐GPL grows much faster, suggesting that it has the potential to outcompete endemic strains (Jenkinson et al., 2018). If this is the case in the wild, the global invasion of the hypervirulent Bd‐GPL may hinder our possibility to detect ancient Bd strains and, thus, truly understand the evolutionary dynamics and spatial epidemiology of this pathogen.…”
Section: Introductionmentioning
confidence: 99%